2022
DOI: 10.1155/2022/5325556
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes of Breast-Conserving Therapy versus Mastectomy in Early-Stage Breast Cancer, Including Centrally Located Breast Cancer: A SEER-Based Study

Abstract: Purpose. This study aims to analyze the survival outcomes of breast cancer (BC) patients, especially centrally located breast cancer (CLBC) patients undergoing breast-conserving therapy (BCT) or mastectomy. Methods. Surveillance, epidemiology, and end results (SEER) data of patients with T1-T2 invasive ductal or lobular breast cancer receiving BCT or mastectomy were reviewed. We used X-tile software to convert continuous variables to categorical variables. Chi-square tests were utilized to compare baseline inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In both the BC and CLBC groups, clinical characteristics such as invasive ductal carcinoma (IDC), lower histologic grade, smaller tumor size, fewer lymph node metastases, positive ER and PR status, and chemotherapy treatment were independently linked with BCT. [19] To address potential confounding variables, techniques of propensity score matching (PSM) and inverse probability of treatment weighting (IPTW). The results of the study indicated that elderly women aged over 70 with larger tumor sizes, higher tumor grades, positive lymph nodes, negative hormone receptor status, and an absence of active local therapy might experience favorable prognostic outcomes from chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In both the BC and CLBC groups, clinical characteristics such as invasive ductal carcinoma (IDC), lower histologic grade, smaller tumor size, fewer lymph node metastases, positive ER and PR status, and chemotherapy treatment were independently linked with BCT. [19] To address potential confounding variables, techniques of propensity score matching (PSM) and inverse probability of treatment weighting (IPTW). The results of the study indicated that elderly women aged over 70 with larger tumor sizes, higher tumor grades, positive lymph nodes, negative hormone receptor status, and an absence of active local therapy might experience favorable prognostic outcomes from chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to mammography screening, a growing number of breast tumors are currently diagnosed in preclinical stage or clinical development. As a consequence, breast conserving surgery (BCS) has become the most used surgical treatment for women with early breast cancer 1–3 . Nonetheless, mastectomy continues to remain a surgical option in selected cases.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, breast conserving surgery (BCS) has become the most used surgical treatment for women with early breast cancer. [1][2][3] Nonetheless, mastectomy continues to remain a surgical option in selected cases. In patients undergoing mastectomy, immediate breast reconstruction (IBR) represents a keystone of the surgical treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches based on real-world data concluded that BCS may be an alternative for CLBC patients. However, these studies had limitations in the study design, including advanced breast cancer, absence of post-surgical radiotherapy, small sample, and insufficient follow-up, which cannot provide evidence for the utility of BCT in patients with early-stage CLBC [ 14 19 ]. Further study is needed to evaluate the long-term oncological safety of BCT in CLBC.…”
Section: Introductionmentioning
confidence: 99%